Child passengers and driver culpability in fatal crashes by driver gender. (3rd July 2016) - Maasalo, Ida; Lehtonen, Esko; Pekkanen, Jami; Summala, Heikki
ABSTRACT: Objective : Studies based on accident statistics generally suggest that the presence of a passenger reduces adult drivers' accident risk. However, passengers have been reported to be a source of distraction in a remarkable portion of distraction-related crashes. Although the effect of passengers on driving performance has been studied extensively, few studies have focused on how a child passenger affects the driver.  A child in a car is a potential distractor for parents, especially for mothers of small children, who often suffer from sleep deficit. The aim of this study was to examine how the presence of child passengers of different ages is associated with a higher driver culpability, which was expected due to child-related distraction and fatigue. Methods : The analysis was based on the comprehensive data of fatal crashes studied in-depth by multidisciplinary road accident investigation teams in Finland during 1988–2012. Teams determine the primary party who had the most crucial effect on the origin of the event. We define the primary party as culpable and the others involved as nonculpable drivers. The culpability rate was defined as the percentage of culpable drivers and rates were compared for drivers with a child/teen passenger aged 0–17 years ( N = 348), with an adult passenger without children ( N = 324), and when driving alone ( N = 579), grouped by child age and driver gender.  Drivers with specific risk-related behavior (substantial speeding, driving when intoxicated, unbelted, or without a license) were excluded from the analyses, in order to make the drivers with and without children comparable. Only drivers 26–47 years old were included, representing parents with children 0–9 years of age. Results : Male drivers were less often culpable with 0- to 17-year-old passengers in the car than alone or with adults. This was not the case with female drivers. The gender difference in culpability was most marked with small children age 0–4 years. Female drivers' culpability rate with a 0- to 4-year-old child passenger was higher and male drivers' culpability rate was lower compared to drivers without passengers or with only adult passengers. Conclusion : The results indicate that female drivers are at higher risk of crashes than male drivers when driving with small children. Further research is needed to replicate this finding and to determine causal mechanisms.